Finding the Best Route for Connecting Citizens with Service Centers in Baghdad Based on NN Technology - Ali, Nibras A.Mohammed; Mohammed, Faisel G.; Mohammed, Sajaa G. (Iraqi Journal of Science, 2024)
A geographic information system (GIS) is a very effective management and analysis tool. Geographic locations rely on data. The use of artificial neural networks (ANNs) for the interpretation of natural resource data has been shown to be beneficial. Back-propagation neural networks are one of the most widespread and prevalent designs. The combination of geographic information systems with artificial neural networks provides a method for decreasing the cost of landscape change studies by shortening the time required to evaluate data. Numerous designs and kinds of ANNs have been created; the majority of them are PC-based service domains. Using the ArcGIS Network Analyst add-on, you can locate service regions around any network site. A network service area is a region that comprises all accessible roadways (that is, routes that are within defined impedance) (that is, streets that are within specified impedance). In contrast to the Google Maps application, the 5-minute service area for a site on a network comprises all streets that can be accessed within five minutes.